STRATEGIES FOR STRENGTHENING THE PROFESIONAL COMPETENCES OF QUR’AN TEACHERS IN DIGITAL ERA - Wahyudi, Wahyudi; Hasyim, Dardiri (STAI Asy-Syukriyyah, 2025)
This study aims to describe the role of teacher competency education in reading and memorizing the Qur'an and its contribution to improving the quality of students' recitation and memorization. This competency education directly correlates with teacher professionalism, which plays a crucial role in the success of the learning process. Using a qualitative approach through literature review, this study finds that professional teachers can motivate students to focus on learning to read and memorize the Qur'an. Teacher professionalism contributes to students’ recitation accuracy, memorization ability, mastery of tajwid, and mental resilience in studying the Qur’an. The findings affirm that strengthening the competence of tahfidz teachers is key to the success of Qur’anic learning programs. This competence development is essential in preserving the Qur’anic heritage and forming a Qur’anic generation.